Pronunciation therapy for deaf students in coping with Arabic letter difficulties - Astari, Rika; Mukhlis, Abdul; Adikistoro, Hanif Cahyo; Purwanti, Tri; Faturrahman, Muhammad Irfan; Yuniawati, Rudy; Mahfud, Choirul (International Journal of Evaluation and Research in Education (IJERE), 2024)
Pronunciation therapy for deaf students is a very important context within the sphere of the Quran learning. Previous investigations in this domain predominantly focused on media and visual approaches, neglecting the discussion of Arabic letter pronunciation therapy (phonetically). Therefore, this research aimed to elucidate various forms of pronunciation therapy designed for deaf students and the underlying factors motivating the use of the therapeutic techniques. This descriptive qualitative research relied on the primary data collected through an investigation conducted at Qotrunnada Islamic Special School (SLB) in Bantul, Yogyakarta, Indonesia. The primary data comprised the diverse methods applied in Arabic letter pronunciation therapy and the determinant factors of articulation disorders. The research subjects were limited to pure deaf students, categorized by age and the length of therapy. Each student exhibited different results of assessment and response to pronunciation therapy. Moreover, data validation was performed through interaction with the school principal as the research team. The results showed that the forms of pronunciation therapy included articulation therapy (phonetically) exercises addressing sound production, as well as interventions targeting attention and behavior for deaf students in coping with Arabic letter difficulties. This contribution would serve as a basic guide in the development of instruments for Arabic letter pronunciation therapy designed for students with special needs.